Molecular Characterization of Paramphistomum cervi in Buffaloes - Rafiq, Naseem; Niaz, Sadaf; Zeb, Ismail; Ayaz, Sultan; Vaz Jr., Itabajara da Silva; Ali, Abid (Acta Scientiae Veterinariae, 2020)
Background: Paramphistomiasis (Rumen fluke disease) in ruminants is a major health problem, while documented reports on Paramphistomum species are limited in Asian countries. The present study aimed to identify paramphistomoid flukes that infects buffaloes with the goal of characterization of prevalence in Pakistan and its comparison with neighbor countries. Materials, Methods & Results: In 2018, a total of 178 slaughtered buffaloes aged four to six years were examined and flukes were collected from their infected rumen and reticulum using sterilized forceps. After amplification and sequencing of 18S rRNA partial fragment, the generated sequences were edited (810bp) and aligned with the other sequences of Paramphistomum species retrieved from NCBI. A phylogenetic tree was constructed using maximum likelihood method in MEGA X. The 18S rRNA sequence was found 100% similar with Paramphistomum cervi of China and 98% with Paramphistomum epiclitum and other Paramphistomum species of India. The parasitic Pharamphistomum species was identified molecularly as P. cervi. Discussion: Molecular studies provide insight into the biology and phylogenetic relationship among various parasites. These studies are reliable in the genetic-based identification and description of several disease causing agents. The 18S rRNA sequence of P. cervi generated in this study was found closely identical to the P. cervi of the neighbor countries (China and India) which may be due to the similar geographical, environmental conditions and transboundary movement of infected hosts. This is the first nature of study which provides the molecular-based evidence of P. cervi existence in Pakistan and revealed the 18S rRNA as novel molecular marker for the identification and further characterization of Paramphistomum species across Pakistan. The submitted sequence of this study will provide a baseline for further molecular characterization and to compare with other Paramphistoma species from different regions of Pakistan.